Organizing the Swedish academic career 1955–2020: reforms and recurring problems in national policy discussion1 - Malin Henningsson (Nordic Journal of Studies in Educational Policy, 2025)
This paper analyzes policy discussion regarding key developments in the national organization of the Swedish academic career during the period 1955–2020. In the 1950s, the academic career was highly regulated and state-planned with a few exclusive academic positions. In 2020, it has become essentially deregulated with universities themselves establishing employment positions. Four key developments are identified: the emergence of parallel careers, the expansion of external research funding, the dramatic increase in professors, and the deregulation of national policy on academic careers. The national policy discussions underpinning these developments are analysed with the help of a theoretical framework for explaining different types of institutional change. The paper shows that changes to the Swedish academic career were undertaken gradually over time, mainly by the layering of new rules over or alongside existing ones as a supplement. In addition, the paper shows that some problems with the academic career have been discussed repeatedly and that even where solutions have been set out, the problems seem to persist.